Design of polyrod and corrugated-rod antennas. - Milligan, Tom
Polyrod (dielectric rod) and corrugated-rod (cigar) antennas radiate from a slow-wave structure that bounds a wave to its surface. The antennas can be excited from a circular waveguide. The author discusses the theory and design of these antennas.
Keywords: Dielectric antennas; Polyrod antennas; Corrugated rod antennas; Slow wave structures; Endfire antennas